Developing and Presenting a Teaching Persona: The Tensions of Secondary Preservice Teachers - Janine Schank Davis (Arizona State University, 2012)
This qualitative, multiple case study investigated the ways that three preservice secondary teachers developed, presented, and considered their teaching personae.  Data for each participant consisted of three interviews, field observations of both teaching and non-teaching, data collection of lessons and class documents, and four journal reflections.  Findings show that the participants experienced various tensions as they formed their teaching personae; as they navigated these tensions, they drew on discourses and ideas about good teaching and their various experiences, including the practicum experience.  The nature of the interactions between the Cooperating Teacher and preservice teacher pairs contributed to the preservice teachers' confidence in and understanding of their enacted personae.  Implications of the research for teacher training programs include an increased need for reflection on persona and careful matching of CIs and student teachers.  Suggestions for further research include investigating the effect of high-quality teacher education programs on persona development and the effects of personae on pupils.